Active Surveillance to Quantify the Burden of Norovirus in a U.S. Veterans Affairs (VA) Patient Population, Houston, 2015–2016. (4th October 2017) - Kambhampati, Anita; Vargas, Blanca; Mushtaq, Mahwish; Browne, Hannah; Perregaux, Sara; Grytdal, Scott; Atmar, Robert L; Vinje, Jan; Parashar, Umesh D; Hall, Aron J; Cardemil, Cristina V; Lopman, Benjamin; et al.
Abstract: Background: Norovirus is the leading cause of acute gastroenteritis (AGE) outbreaks in the United States; however, little data exist on the burden of endemic norovirus disease among adults. Robust estimates of the norovirus disease burden among US adults are needed to inform assessment of potential norovirus vaccines, which are currently in development. Methods: We conducted active surveillance for AGE at the Michael E. DeBakey Veteran's Affairs (VA) Medical Center, where approximately 104, 000 unique patients were served in 2016. Cases were defined as veterans with symptoms of AGE (≥3 loose stools, ≥2 vomiting episodes, or ≥1 episodes of both loose stool and vomiting, within 24 hours) occurring in the previous 10 days, who presented to the emergency department or outpatient clinics (outpatients), or were admitted to the hospital (inpatients). Patients without AGE symptoms in the prior 14 days were enrolled as controls. Demographic data and illness characteristics were collected from enrolled subjects, and stool samples were collected and tested using the FilmArray gastrointestinal panel. Norovirus positives were confirmed by real-time RT-PCR and genotyped after sequencing of conventional PCR products. Results: From November 1, 2015–November 30, 2016, 130 inpatient and 85 outpatient AGE cases, along with 20 inpatient and 37 outpatient controls, were enrolled and provided a stool specimen. Among cases, 201 (93%) were male, and 94 (44%) were ≥65 years; median duration of illness was 3 days (range, 1–10 days). Norovirus was detected in 12 (9%) inpatient and 15 (18%) outpatient cases; norovirus was not detected in any controls. Incidence of norovirus-associated hospitalization was 15/100, 000 population, and was similar in hospitalized cases aged <65 years (14/100, 000) and ≥65 years (15/100, 000). Of 22 norovirus positive specimens genotyped, 13 (59%) were GII.4 Sydney. Conclusion: This robust, active surveillance platform employed screening and enrollment of patients in a VA population meeting a standardized AGE case definition, as well as asymptomatic controls. Data from this study highlight the burden of norovirus in adults and importance of a norovirus vaccine. Disclosures: R. L. Atmar, Takeda Vaccines, Inc.: Research Support, Research support. B. Lopman, HHS/NIH/NIAID: Grant Investigator, Grant recipient. Bill & Melinda Gates Foundation: Grant Investigator, Grant recipient.